Migration of Sri Lankan medical specialists - De Silva, A.P.; Liyanage, I.K.; De Silva, S.T.G.; Jayawardana, M.B.; Liyanage, C.K.; Karunathilake, I.M. (BMC - Springer Nature, 2013)
Abstract Background: The migration of health-care workers contributes to the shortage of health-care workers in many developing countries. This paper aims to describe the migration of medical specialists from Sri Lanka and to discuss the successes and failures of strategies to retain them. Methods: This paper presents data on all trainees who have left Sri Lanka for postgraduate training through the Post Graduate Institute of Medicine, University of Colombo, from April 1980 to June 2009. In addition, confidential interviews were conducted with 30 specialists who returned following foreign training within the last 5 years and 5 specialists who opted to migrate to foreign countries. Results: From a total of 1,915 specialists who left Sri Lanka for training, 215 (11%) have not returned or have left the country without completing the specified bond period. The majority (53%) migrated to Australia. Of the specialists who left before completion of the bond period, 148 (68.8%) have settled or have started settling the bond. All participants identified foreign training as beneficial for their career. The top reasons for staying in Sri Lanka were: job security, income from private practice, proximity to family and a culturally appropriate environment. The top reasons for migration were: better quality of life, having to work in rural parts of Sri Lanka, career development and social security. Conclusions: This paper attempts to discuss the reasons for the low rates of emigration of specialists from Sri Lanka. Determining the reasons for retaining these specialists may be useful in designing health systems and postgraduate programs in developing countries with high rates of emigration of specialists
Keywords: Migration of health-care workers; Health-care worker shortage; Training of medical specialists